2021
DOI: 10.1038/s41598-021-97520-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on hypofractionated whole-breast irradiation with sequential or simultaneous integrated boost on different positions after breast-conserving surgery

Abstract: This study explored the dosimetric difference between hypofractionated whole-breast irradiation (HFWBI) with sequential boost (SEB) and simultaneous integrated boost (SIB) based on supine and prone positions to identify the superior boost mode and superior position. Thirty breast cancer patients eligible for HFWBI after breast-conserving surgery were enrolled. All patients underwent 3DCT simulation scanning in both supine and prone positions. For the SEB-HFWBI plan, the dose prescribed for the planning target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…As a pioneering study utilizing H-VMAT when comparing dosimetric parameters between SEQ-HFWBI and SIB-HFWBI, we found the CI value for both plans was close to 1, aligning with the ideal value as suggested by previous studies. Additionally, the HI analysis indicated that the SIB plans exhibited better dose homogeneity for the tumor bed (PTVtb) and the whole breast excluding the tumor bed (PTVwb-tb) compared to the SEQ plans, consistent with ndings from Yu et al [17].…”
Section: Dosimetric Evaluationsupporting
confidence: 84%
“…As a pioneering study utilizing H-VMAT when comparing dosimetric parameters between SEQ-HFWBI and SIB-HFWBI, we found the CI value for both plans was close to 1, aligning with the ideal value as suggested by previous studies. Additionally, the HI analysis indicated that the SIB plans exhibited better dose homogeneity for the tumor bed (PTVtb) and the whole breast excluding the tumor bed (PTVwb-tb) compared to the SEQ plans, consistent with ndings from Yu et al [17].…”
Section: Dosimetric Evaluationsupporting
confidence: 84%
“…Few reports are available on the dosimetric feasibility of HF-SIB, which has not yet been widely adopted clinically for breast cancer. Yu T et al [ 28 ] dosimetrically compared HF-WBI with SEQ versus SIB in the supine and prone positions using three-dimensional conformal RT with the field-in-field technique. The dose prescribed for WBI was 40.05 Gy in 15 fractions, while that of the tumor bed was 9.6 Gy in 3 fractions for SEQ and 48 Gy in 15 fractions for SIB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent emphasis on the significance of preoperative MRI selection has been highlighted across various tumor radiotherapy contexts 23,24 . Prone positioning during whole‐breast radiotherapy offers advantages such as improved target conformity, dose homogeneity, reduced dose to organs at risk, and mitigation of acute radiation skin injury, 25,26 especially in patients with larger breasts 27–30 . Consequently, radiotherapy in the prone position after BCS is increasingly being used in patients with early‐stage breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Prone positioning during whole-breast radiotherapy offers advantages such as improved target conformity, dose homogeneity, reduced dose to organs at risk, and mitigation of acute radiation skin injury, 25,26 especially in patients with larger breasts. [27][28][29][30] Consequently, radiotherapy in the prone position after BCS is increasingly being used in patients with early-stage breast cancer. This study aimed to investigate the use of preoperative MRI in guiding LC delineation in patients with BCS.…”
Section: Correlation Analysismentioning
confidence: 99%